2022
DOI: 10.1111/cob.12555
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying patients' expectations prior to bariatric surgery with the BODY‐Q in an international multicentre cohort

Abstract: Summary Many people living with obesity may have unrealistic expectations prior to undergoing bariatric surgery. These expectations can lead to frustration, regret and even worse psychological outcomes after surgery. Prior to undergoing bariatric surgery, patients completed the BODY‐Q Expectations scale. This 15‐item scale asks patients to imagine what their life will be like when 2 years have passed since bariatric surgery. Scores for expectations range from 0 (low) to 100 (high). Linear regression models wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…However, the %TWL did not differ between the age groups. These ndings contradict previous studies indicating that younger patients tend to have higher expectations regarding weight loss (20,21). A potential explanation could be that younger patients typically have fewer comorbidities, allowing them to focus more on weight loss.…”
Section: Discussioncontrasting
confidence: 94%
“…However, the %TWL did not differ between the age groups. These ndings contradict previous studies indicating that younger patients tend to have higher expectations regarding weight loss (20,21). A potential explanation could be that younger patients typically have fewer comorbidities, allowing them to focus more on weight loss.…”
Section: Discussioncontrasting
confidence: 94%
“…Expectations for BS is another important consideration for preoperative support because participants in the current review highlighted discrepancies between their expectations of BS and perceived reality postsurgery. Similarly, a recently published study by Dijkhorst et al 32 investigated pre‐surgical patients' expectations of life following BS, using a scale score in which 61 participants (18.5%) scored at the ceiling for the scale (i.e., 100), indicating high expectations for how their life would be after surgery. Improvements in physical health, appearance, confidence and happiness levels were rated the highest among participants.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In addition, the expected results of bariatric surgery might be overestimated by patients, leading to frustration and dissatisfaction. [7][8][9] As a result, individuals may experience decision regret after bariatric surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that a small proportion of individuals may experience negative outcomes after bariatric surgery including suboptimal weight loss, surgical complications or decreased quality of life (QoL) 5,6 . In addition, the expected results of bariatric surgery might be overestimated by patients, leading to frustration and dissatisfaction 7–9 . As a result, individuals may experience decision regret after bariatric surgery.…”
Section: Introductionmentioning
confidence: 99%